The effect on the knock intensity of high viscosity biodiesel use in a DI diesel engine - SAYIN, CENK (ELSEVIER SCI LTD, 2019)
In this study, the effect of usage of biodiesel fuel with higher viscosity on the engine knock intensity was investigated. The animal biodiesel (AB) and the vegetable biodiesel (VB) were used as fuel in the study. It was seen that the AB had a high viscosity, while the viscosity of VB is within the limits determined by the standards (EN 14214 and ASTM D6751). In the engine tests carried out at constant engine speed and high load, ringing intensity (RI) and knock intensity values were found with in-cylinder pressure data obtained from three fuel types. In addition, the in-cylinder gas pressure, heat release rate and cumulative heat release curves for the three fuel types are presented. According to the results, the effects of high viscosity biodiesel usage on these values were found to be limited. It was also observed that the RI was lower than that of D2 and higher than that of VB.
Keywords: Vegetable biodiesel (VB); Animal biodiesel (AB); Cylinder gas pressure; Knock intensity; Ringing intensity; FUEL PROPERTIES; METHYL-ESTER; PERFORMANCE; COMBUSTION; BLENDS; EMISSIONS